Description of the advertisement call of Dendropsophus haddadi (Bastos and Pombal 1996) (Anura: Hylidae) from southern Bahia, Brazil - Ruas, Danilo Silva; de Mira Mendes, Caio Vinicius; Dias, Iuri Ribeiro; Solé, Mirco (Zootaxa, 2012)
The Dendropsophus decipiens clade is part of the Dendropsophus microcephalus group, and currently comprises four species: D. berthalutzae, D. decipiens, D. haddadi and D. oliveirai (Faivovich et al. 2005; Frost 2011). According to Faivovich et al. (2005) the phenotypic synapomorphies of this clade are the oviposition on leaves overhanging water and the presence of a posterior row of marginal papillae in the tadpoles. Dendropsophus haddadi can be found in the Coastal Atlantic Rainforest, and in the scrubby "restinga" vegetation between eastern Espírito Santo and Pernambuco states (Bastos & Pombal 1996; Amorim et al. 2009).